Novel sensor suit design for smart suit : technology, ergonomics and fashion - Low, Kien Ooi. (2009)
The modern society has an increasing demand on the human processing system for real time sensing and processing of human anatomical motion. Research and development has thus been conducted to investigate the various methods of sensing to meet these needs. In this particular project, mechanical assistive device with optical fiber technology was adopted to detect the human motion and translate the information to an operating system for further processing. However, a sensing device without proper packaging will not perform to its optimum potential. Hence, a “suit” was proposed in this project to fully optimize the performance of the devices, known as the Smart Suit. The Smart Suit is an intelligent suit with linear encoding sensors embedded within it to detect the change in human motion. This information will then be translated to a software to reproduce the human motion in a virtual environment, with a virtual character responding coherently with the user’s movements. In this report, the author will further elaborate on the design of the Smart Suit, and decision to produce the suit in a modular form. The goal of the project is to produce a final prototype of the Smart Suit which is ergonomic, fashionable, and yet functional. The design process will start off with the design consideration and proposed solution at the conceptual stage, followed by the discussion of the advantages and disadvantages of several mock up designs. The final prototype of the Smart Suit will then be fabricated after analyzing these mock up models. This will then be followed by conducting of standard testing procedures on the final prototype to determine it’s ergonomic and functionality on the user. Feedbacks will then be recorded and analyzed, followed by provision of suggestions for further improvements on the prototype. Possible modifications will then be made on the existing prototypes. Illustrations of future development on the lower limb will be presented on the later chapters with sketches and 3D models.